The Influence of Feeling Lonely and Received Social Support on Medication Adherence in Elderly with Hypertension - Dwi Novita Sari; Wahyu Utami; Elida Zairina (Universitas Airlangga, 2022)
Background: Hypertension is currently a non-contagious disease that primarily affects the elderly population in Indonesia. Medication adherence is critical in managing hypertension and reducing the risk of morbidity and mortality. Previous research has found that loneliness and support received by older adults with hypertension influence medication adherence. Objective: This study aimed to examine the impact of feeling lonely and receiving social support on medication adherence in the elderly with hypertension at the Community Health Center in Surabaya. Methods: The study design of this research was a descriptive cross-sectional study from December 2021 to March 2022. A total of 235 eligible subjects fulfilled the inclusion criteria. The instruments used in the data collection were the patient's information form, UCLA-Loneliness Scale, MOS-Social Support Survey, and the ARMS (Adherence to Refill and Medication Scale). Results: The results revealed that the correlation between loneliness and social support was significantly associated with medication adherence in the elderly with hypertension (p < 0.05). In addition, other factors, such as occupation status, living status, comorbidity, the number of drugs taken, and antihypertensive drug therapy, showed a significant correlation with medication adherence (p < 0,05). The most influential factor on medication adherence was loneliness (35.5%), followed by social support (24.4%), the number of drugs taken (7.1%), antihypertensive drug therapy (monotherapy or combination therapy (2.5%), occupation status (2.4%), comorbidity (1.6%), and living status (0.2%). Conclusion: This study confirms that feeling lonely and receiving social support affect medication adherence in the elderly with hypertension at the Community Health Center in Surabaya.